THU0067 Analysis of autoantigens recognised by autoantibodies that immunoprecipitate high molecular weight nucleic acids. (1st June 2001) - Suzuki, M; Hirakata, M; Suwa, A; Nojima, T; Yasuoka, H; Satoh, S; Fujii, T; Inada, S; Mimori, T
Abstract : Background: A number of sera from patients with connective tissue diseases that immunoprecipitated high molecular weight (hmw) nucleic acid smear have been found in RNA-immunoprecipitation (IPP) assay. Most of these sera are supposed to contain autoantibodies for DNA- or mRNA- (or its precursor) related proteins. However, neither the characteristics of antigens nor the clinical significance have been well-defined. Objectives: To analyse the corresponding antigens for autoantibodies immunoprecipitating hmw-nucleic acid smear and to elucidate the clinical features associated with these autoantibodies. Methods: We examined 63 sera from patients with various kinds of connective tissue diseases that immunoprecipitated hmw nucleic acid smear by RNA-IPP. IPP using [35S] methionine-labelled HeLa cell extracts was performed for analysis of the protein components. Immunoprecipitated nucleic acid components were treated with DNase I or RNase A to identify either DNA or RNA. Results: DNA and a heterodimer of 70 kDa and 80 kDa proteins (p70/p80) that was identified as the Ku antigen, was immunoprecipitated by 16 patient sera (4:SLE, 7: myositis overlap syndrome, 1: interstitial pneumonia (IP), 4: undiagnosed). In addition, DNA-protein complex consisting of four polypeptides (11 kDa-21 kDa) that appeared to be histone core proteins, was immunoprecipitated by 18 sera (12:SLE including one drug-induced lupus, 5:MCTD/overlap syndrome, 1: autoimmune hepatitis). Eight patients sera (5:SLE, 2:RA, 1:IP) reacted with the 140 kDa protein along with hmw-RNA smear that was supposed to be RNA helicase A. It should be noted that the remaining 37 of 63 (59%) patients sera immunoprecipitated none of proteins with defined specificities, but various unidentified proteins. Conclusion: Autoantibodies to the Ku, histone, and RNA-helicase A have been identified in patients sera with SLE and other rheumatic diseases that immunoprecipitated hmw-nucleic acid smear. However, a high percentage of these sera were found to contain novel hmw nucleic acids-related antibodies. Further analysis of these autoantibodies may provide clues for understanding the pathogenic mechanism of connective tissue diseases.